The expanding importance of tissue sample analysis for biomarker testing in non-small cell lung cancer management and survival - Augusto Valdivia; Ilaria Priano; Nuria Pardo; Enriqueta Felip (Barcelona Respiratory Network Reviews, 2024)
Non-small-cell lung cancer (NSCLC) is the most frequent type of lung cancer, currently a leading cause of cancer-related death worldwide. The development of molecular biomarkers has led to novel treatment strategies and subsequent improvement in survival outcomes in all stages of the disease.